2019
DOI: 10.1038/s41598-019-41065-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrative comparative analyses of metabolite and transcript profiles uncovers complex regulatory network in tomato (Solanum lycopersicum L.) fruit undergoing chilling injury

Abstract: Tomato fruit are especially susceptible to chilling injury (CI) when continuously exposed to temperatures below 12 °C. In this study, integrative comparative analyses of transcriptomics and metabolomics data were performed to uncover the regulatory network in CI tomato fruit. Metabolite profiling analysis found that 7 amino acids, 27 organic acids, 16 of sugars and 22 other compounds had a significantly different content while transcriptomics data showed 1735 differentially expressed genes (DEGs) were down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…Citrate, the first intermediate involved in the TCA cycle, is known to participate in plants responses to abiotic stress. The increase in citrate accumulation was observed in cotton under drought [52] and tomato under chilling treatment [53]. Wu et al demonstrated that citrate has the anti-oxidant capacity to modulate redox signaling through scavenging free radicals and chelating iron ions [54].…”
Section: Exogenous Cor Enhances the Accumulation Of Organic Acids Undmentioning
confidence: 99%
“…Citrate, the first intermediate involved in the TCA cycle, is known to participate in plants responses to abiotic stress. The increase in citrate accumulation was observed in cotton under drought [52] and tomato under chilling treatment [53]. Wu et al demonstrated that citrate has the anti-oxidant capacity to modulate redox signaling through scavenging free radicals and chelating iron ions [54].…”
Section: Exogenous Cor Enhances the Accumulation Of Organic Acids Undmentioning
confidence: 99%
“…Sebastian and Prasad reported that supplementation with citrate and malate could alleviate cadmium stress by reducing Cd-induced iron nutrition deficiency in rice 38 . The accumulation of citrate and malate was also detected in plants under cold conditions 29,39 . α-Ketoglutarate bridges the metabolism of carbohydrates and amino acids, serving as a precursor for the biosynthesis of glutamate and proline and subsequent protein biosynthesis.…”
Section: Discussionmentioning
confidence: 91%
“…The accumulation of amino acids is a common occurrence in many plant species when subjected to cold stress [28][29][30] , reflecting amino acid production or related protein degradation. It is thought that many amino acids that are specifically enriched in plants have a beneficial function during stress acclimation 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…role in cold tolerance in plants 45,51 . Amongst the different TCA cycle metabolites, the levels of citrate were significantly higher (p = 0.019; FC = 0.54) in the processing cultivar, FL-1533; whereas Kufri Jyoti and Kufri Pukhraj showed significantly higher levels of malate after CS (Fig.…”
Section: Tca Cycle Metabolites Under Cold Storage Condition Organic mentioning
confidence: 99%